Potential of Krebs von den Lungen‐6 as a predictor of relapse in interstitial pneumonia with anti‐aminoacyl tRNA synthetase antibodies‐positive dermatomyositis. (1st August 2018) - Isoda, Kentaro; Kotani, Takuya; Takeuchi, Tohru; Konma, Junichi; Ishida, Takaaki; Hata, Kenichiro; Otani, Kenichiro; Fujiwara, Hiroshi; Shoda, Takeshi; Makino, Shigeki; Arawaka, Shigeki
Abstract: Objective: To identify a predictor of relapse in interstitial pneumonia (IP) in patients with anti‐aminoacyl tRNA synthetase antibodies‐positive dermatomyositis (ARS‐DMIP). Methods: This retrospective cohort study comprised 27 ARS‐DMIP patients. We compared clinical and laboratory findings between the relapse and non‐relapse groups during 2 years after treatment initiation to find predictors of relapse in IP. Candidate predictors were further assessed by analysing the relationship with the relapse of IP. Results: One patient with ARS‐DMIP died. About 7 (26.9%) of the remaining 26 patients with ARS‐DMIP had a relapse of IP. We found that the levels of serum Krebs von den Lungen‐6 (KL‐6) in the relapse group were significantly higher than those in the non‐relapse group at the time points before treatment ( P = .046) and after treatments, including 6 ( P = .004), 12 ( P = .013), 18 ( P = .003) and 24 months ( P < .001). The KL‐6 values that maximised the area under the ROC curve were 2347 U/mL before treatment, 622 U/mL after 6 months and 468 U/mL after 12 months. The relapse rates after 104 weeks were significantly higher in patients with KL‐6 levels ≥2400 U/mL before treatment ( P = .014), ≥600 ng/mL after 6 months ( P < .005) and ≥470 U/mL after 12 months ( P = .010). Conclusion: These findings suggest that the levels of KL‐6 before and after treatment in ARS‐DMIP may represent the disease activity of IP, and they may be useful as the predictor of relapse in IP in patients with ARS‐DMIP.